2010
DOI: 10.1186/1471-2148-10-86
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for a diverse green algal community growing in the hair of sloths and a specific association with Trichophilus welckeri(Chlorophyta, Ulvophyceae)

Abstract: BackgroundSloths are slow-moving arboreal mammals inhabiting tropical rainforests in Central and South America. The six living species of sloths are occasionally reported to display a greenish discoloration of their pelage. Trichophilus welckeri, a green algal species first described more than a century ago, is widely believed to discolor the animals fur and provide the sloth with effective camouflage. However, this phenomenon has not been explored in any detail and there is little evidence to substantiate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 21 publications
2
85
3
3
Order By: Relevance
“…A cryptic diversity of 'green balls' was discovered in manifold aquatic and terrestrial habitats, resulting in the designation of new genera and species [8,9]. New strains with interesting physiological and biochemical features were discovered from exotic habitats, such as salty, acidic, or alkaline waters, leaves of tropical rainforest trees, and the pelt of sloths [9,10]. For a long time, ecologists were unaware of the wide diversity of the spherical green algae, although Chlorella and its relatives belong to the most common aquatic, terrestrial, and aerophytic algae with ubiquitous distribution.…”
Section: Modern Systematics Supports New Insights Into Science and Apmentioning
confidence: 99%
“…A cryptic diversity of 'green balls' was discovered in manifold aquatic and terrestrial habitats, resulting in the designation of new genera and species [8,9]. New strains with interesting physiological and biochemical features were discovered from exotic habitats, such as salty, acidic, or alkaline waters, leaves of tropical rainforest trees, and the pelt of sloths [9,10]. For a long time, ecologists were unaware of the wide diversity of the spherical green algae, although Chlorella and its relatives belong to the most common aquatic, terrestrial, and aerophytic algae with ubiquitous distribution.…”
Section: Modern Systematics Supports New Insights Into Science and Apmentioning
confidence: 99%
“…The group is predominantly marine, but several transitions to freshwater or terrestrial habitats have occurred independently (Shimada et al, 2008;Ichihara et al, 2009;Suutari et al, 2010). The orders Ulvales and Ulotrichales have traditionally been distinguished based on life history features: the Ulvales have a life cycle involving isomorphic alternations of multicellular stages, while in the Ulotrichales the diploid, spore-producing stage is a small, thick-walled unicell that is attached to the substrate by a stalk (Codiolum stage) (O'Kelly et al, 2004b).…”
Section: Ulvophyceaementioning
confidence: 99%
“…The landmark article by Woese and Fox (1977) demonstrated that the presence of ribosomal RNA (rRNA) in all living organisms and its high degree of conservation make it an excellent gene for studying species relationships. Since then, rRNA has been a popular choice for phylogenetic inference, ranging from the algae that live on sloth fur (Suutari et al 2010) to 200 metazoan species (Mallatt et al 2010). The biological importance of rRNA (and tRNA) is well established, but recently the significance of other types of noncoding RNA (ncRNA) has been recognized (reviewed in Griffiths-Jones 2007;Mattick 2009).…”
Section: Introductionmentioning
confidence: 99%